2014
DOI: 10.1111/mec.12613
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of hybrid zones at different stages of speciation in the common vole (Microtus arvalis)

Abstract: The genetic structure and dynamics of hybrid zones provide crucial information for understanding the processes and mechanisms of evolutionary divergence and speciation. In general, higher levels of evolutionary divergence between taxa are more likely to be associated with reproductive isolation and may result in suppressed or strongly restricted hybridization. In this study, we examined two secondary contact zones between three deep evolutionary lineages in the common vole (Microtus arvalis). Differences in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 76 publications
2
84
2
1
Order By: Relevance
“…We can also determine whether geographic structure revealed by microsatellites is in agreement with the mtDNA lineage distributions across Poland found in previous studies (Herman et al 2014, Stojak et al 2015. For one of these species, the common vole, studies from other regions in Europe have already found general congruence in patterns of genetic structure between mtDNA and microsatellites at contacts between lineages (Heckel et al 2005;Braaker and Heckel 2009;Beysard and Heckel 2014). For the field vole, Beysard et al (2012) demonstrated an overall pattern of congruence between mtDNA, microsatellites and Laboratory procedures were repeated three times for each sample and each locus.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We can also determine whether geographic structure revealed by microsatellites is in agreement with the mtDNA lineage distributions across Poland found in previous studies (Herman et al 2014, Stojak et al 2015. For one of these species, the common vole, studies from other regions in Europe have already found general congruence in patterns of genetic structure between mtDNA and microsatellites at contacts between lineages (Heckel et al 2005;Braaker and Heckel 2009;Beysard and Heckel 2014). For the field vole, Beysard et al (2012) demonstrated an overall pattern of congruence between mtDNA, microsatellites and Laboratory procedures were repeated three times for each sample and each locus.…”
Section: Discussionsupporting
confidence: 72%
“…1). Beysard and Heckel (2014) analysed the genetic structure and dynamics of three contact zones between mitochondrial lineages of the common vole located in Switzerland and Bavaria. They found very narrow zones of hybridization (using microsatellites) between the Central and Western lineages and a much wider hybrid zone between the Central and Eastern lineages (which are the lineages present in Poland; Stojak et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons among examples with different overall barriers and different combinations of barrier effects, as well as comparative analyses of replicated and independent events of contact in a given system can also help this reconstruction (e.g., Nadeau et al 2014;Vijay et al 2017). In general, it will be important to identify more systems offering multiple hybrid zones to compare situations where coupling may not be at the same stage across the distribution range (e.g., in common voles [Beysard and Heckel 2014], Hyla frogs [Dufresnes et al 2015], or green toads [Dufresnes et al 2014]). Combining genomic analysis of such systems with analysis of phenotypes and the types of barrier effects (one allele vs. two allele) is the most likely route toward understanding of coupling processes.…”
Section: Distinguishing Among Coupling Processesmentioning
confidence: 99%